Signs of enhanced formation of gist memory in children with autism spectrum disorder – a study of memory functions of sleep. (25th March 2019) - Kurz, Eva‐Maria; Conzelmann, Annette; Barth, Gottfried Maria; Hepp, Lisa; Schenk, Damaris; Renner, Tobias J.; Born, Jan; Zinke, Katharina
Abstract : Background: Autism spectrum disorder (ASD) is characterized by impaired cognitive and social skills, including emotional dysregulation, and symptoms have been suspected to partly arise from impaired formation of memory representations regulating these behaviours. Sleep, which is subjectively impaired in ASD, is critical for forming long‐term memories and abstracted gist‐based representations. We expected a generally reduced memory benefit from sleep in children with ASD, and a diminished enhancement of gist representations, in particular. Methods: We compared effects of sleep on memory consolidation between boys (9–12 years) with ASD ( n = 21) and typically developing (TD, n = 20) boys, matched for age and IQ, in a within‐subjects crossover design. We employed an emotional picture recognition task and the Deese–Roediger–McDermott (DRM) word list task for assessing gist memory formation in the emotional and nonemotional domain, respectively. Learning took place before retention intervals of nocturnal sleep and daytime wakefulness, and retrieval was tested afterwards. Results: Surprisingly, on the DRM task, children with ASD showed an enhanced sleep‐dependent formation of gist‐based memory (i.e. more recall of 'critical lure words' after sleep compared to wakefulness) than TD children, with this effect occurring on top of a diminished veridical word memory. On the picture recognition task, children with ASD also showed a stronger emotional enhancement in memory (i.e. relatively better memory for negative than neutral pictures) than TD children, with this enhancement occurring independent of sleep. Sleep polysomnography was remarkably comparable between groups. Conclusions: Children with ASD show well‐preserved sleep‐dependent memory consolidation. Enhanced gist memory formation in these children might reflect a compensatory response for impairments at earlier stages of memory processing, that is during encoding.